A Comparative Study of Different Properties of Commercial Dental Composite Resins in the Market - Golnaz Tayebi; Sajjad Omidian; Sara Abtahi; Alireza Ranjbar Hassani; Yasaman Sherafatmand (Tehran University of Medical Sciences, 2024)
Objectives: Assessment of mechanical properties of composite resins is important since they can affect the clinical performance and longevity of restorations. This study aimed to assess and compare different properties of dental composite resins available in the market. Materials and Methods: In this comparative study, samples of four different dental composite resins (Edge COM, Saremco, FGM, and Kulzer) were tested according to ISO 4049:2019 guidelines. Flexural strength (by using a universal testing machine), depth of cure (using the ISO 4049 scrape technique), radiopacity (with aluminum step wedge), water sorption/solubility (by using immersion and drying cycles), and shade (by using Vita Easy Shade) of the samples were assessed. Data were analyzed by one-way ANOVA and Tukey's post-hoc test (alpha=0.05). Results: No significant difference was found in flexural strength among the four groups (P>0.05). The depth of cure of FGM was significantly higher than that of other groups (P<0.05). Solubility and water sorption were the highest in Kulzer, and the lowest in Edge COM (P<0.05). All tested composites met the necessary radiopacity standards for precise radiographic diagnosis; radiopacity was higher in Saremco and FGM groups. None of the composite resins matched the reference A2 shade. Conclusion: Although no significant difference was found in flexural strength of the tested composites, they had differences in other properties. Edge COM exhibited high flexural strength, while Saremco had optimal radiopacity.